Understanding the Psychosocial Influences on High School Football Players' Weight-Gaining Behaviors. Issue 1 (1st January 2017) - Head, Katharine J.; Iannarino, Nicholas T.
Abstract : High school football players are often encouraged to "bulk up" to improve their performance. However, their weight-gain techniques often include unhealthy eating practices that have health consequences. Using the integrated behavioral model (IBM) as a sensitizing framework, we interviewed 22 former high school football players. Findings indicate significant descriptive and injunctive normative influences, a culture of high school football that facilitated bulking up, and contrasting experiential and instrumental attitudes toward weight-gain behaviors. This formative research can assist in the development of health communication interventions targeting players, coaches, and parents.